2021
DOI: 10.1111/cen.14449
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent menstrual disorder after spontaneous menarche in Turner syndrome

Abstract: Objective Turner syndrome (TS) is a congenital disease characterized by delayed puberty, ovarian dysgenesis and short stature. Although most patients are diagnosed with primary amenorrhea, approximately 15‐20% of patients with TS are reported to have spontaneous menarche. However, little is known about their menstruation status after spontaneous menarche. In the current study, we investigated the menstrual abnormalities after spontaneous menarche in TS patients. Design Retrospective study. Patients This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Actually, a previous systematic review reported a 66.2% rate of spontaneous menarche in mosaic TS patients, while 20.8% for overall TS patients (Dabrowski et al, 2019). Also, Komura et al (2021) witnessed a 37.5% prevalence of POI after menarche, with a median menopause age of 20. The average duration from menarche to menopause was only 5.1 years in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, a previous systematic review reported a 66.2% rate of spontaneous menarche in mosaic TS patients, while 20.8% for overall TS patients (Dabrowski et al, 2019). Also, Komura et al (2021) witnessed a 37.5% prevalence of POI after menarche, with a median menopause age of 20. The average duration from menarche to menopause was only 5.1 years in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…TS is mainly characterized by short stature, delayed puberty, and ovarian dysgenesis (Komura et al, 2021). Almost all women with TS suffer from hypergonadotropic hypogonadism, contributing to primary or secondary amenorrhea and infertility ultimately (Gravholt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This was a cross-sectional study of 95 TS patients. Although the main clinical feature of most TS patients is premature ovarian insufficiency [ 13 , 22 ], some patients still experience spontaneous puberty [ 23 ]. Serum AMH levels have been shown to reflect ovarian reserves in adult women with TS [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The onset, severity, and clinical presentation of ovarian failure is highly variable. Spontaneous thelarche occurs in 21-50% of Turner syndrome adolescents whereas spontaneous menarche occurs in 15-30% [71,72]. Although strict genotype/phenotype correlations for ovarian function do not exist, there is general consensus that mosaic karyotypes are more likely to have ovarian function [73][74][75].…”
Section: Incidencementioning
confidence: 99%